2012
DOI: 10.1589/jpts.24.809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neurofeedback on Brain Waves and Cognitive Functions of Children with Cerebral Palsy: a Randomized Control Trial

Abstract: Abstract. [Purpose] This study investigated brain wave and cognitive function changes in children with cerebral palsy (CP) using neurofeedback (NFB).[Subjects] Twenty-eight children with CP were randomly allocated to the NFB (n = 14) and control (CON) (n = 14) groups.[Methods] Two expert therapists provided the NFB and CON groups with traditional rehabilitation therapy in 30-minute sessions, semi-weekly, for 6 weeks. NFB training was provided only to the NFB group. The CON group received traditional rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…6). Because SEF50 is the frequency below 50% of the total EEG power (Schwender et al, 1996), it is a measure used to investigate the activity of the cerebral cortex and indicates the degree of workload (Yu et al, 2012). The SEF50 is an index for the awake state that shows how much of the brain is active during a task (Schwarz et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). Because SEF50 is the frequency below 50% of the total EEG power (Schwender et al, 1996), it is a measure used to investigate the activity of the cerebral cortex and indicates the degree of workload (Yu et al, 2012). The SEF50 is an index for the awake state that shows how much of the brain is active during a task (Schwarz et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ratio of beta and theta power (RBT) was calculated by ratio of power in the 4-to 7-Hz band to power in the 14 to 30 Hz. The SEF50 is the frequency of the point on the power spectrum graph in which the area from 4 to 50 Hz occupies 50% of the area in the entire frequency range (Yu et al, 2012). To determine the effect of the presence of foliage plants on assignment performance, the number of questions solved and the number of correct answers per total number of questions were calculated as a percentage using Microsoft Excel (Office 2007; Microsoft Corp., Redmond, WA).…”
Section: Methodsmentioning
confidence: 99%
“…This study explores the feasibility and effectiveness of EEG neurofeedback to address AD in children with CP. Previous studies have utilized EEG neurofeedback treatment to determine its effectiveness on motor functions or cognitive abilities in children with CP (e.g., Alves‐Pinto et al, 2017; Yu et al, 2012). These studies generally demonstrated increased motor function or cognitive abilities by using the feedback of different frequency bands.…”
Section: Introductionmentioning
confidence: 99%
“…We calculated and analyzed the RLB and RFA power spectra by the ratio of power in the 4 to 50 Hz band to power in the 12 to 15 Hz and 11 to 13 Hz, respectively [40]. We analyzed SEF50 as the frequency of the point on the power spectrum graph where the region from 4 to 50 Hz occupies 50% of the region in the entire frequency range [41]. We analyzed ASEF50 as the frequency of the point on the power spectrum graph where the region from 8 to 13 Hz occupies 50% of the region in the entire frequency range.…”
Section: Data Processing and Analysismentioning
confidence: 99%